Entrepreneurship and After Life : How Does the Job Market Respond to Entrepreneurs Seeking Opportunities After the Death of Their Ventures? - Soni, Bhavya; Soni, Sumedha (AMC Indian Journal of Entrepreneurship, 2021)
Purpose : The paper aims to explore corporate response to job seekers having entrepreneurial experience. 9 out of 10 entrepreneurial ventures fail within five years of their ignition in India. This pushes many entrepreneurs to switch their roles from job providers to job seekers. When entrepreneurs shut their shops and join job market as job seekers they possibly have to face some unique challenges or opportunities on account of their entrepreneurial experience. Corporate may respond to them in different ways and treat their entrepreneurial experience, mindset and skill set with some incredulity. This research paper aims to improve our understanding of how does job market respond to former entrepreneurs seeking job opportunities? Also what could be potential sources of unique challenges faced during this pursuit of a job? Major Findings : There are inconsistencies in the way candidates with entrepreneurial experience are treated by the job market across Tier I, II and III cities. Candidates with entrepreneurial experience are more welcomed at the top level of the organizational pyramid if they have experience of significant number of years. Some degree of prior corporate work experience in addition to the entrepreneurial experience is more preferred by corporates. Freelance economy also provides an opportunity for former entrepreneurs to provide their skills to employers. Practical Implications : This paper recommends five Action Points to the stakeholders of entrepreneurial ecosystem including incubation centers, educational institutions, corporates and startup mentors to ensure effective support system for safer landing (or crashing) of entrepreneurs after the death of their ventures. Social implications : This paper has the potential to ignite interaction and integration among various stakeholders of entrepreneurial ecosystem to ensure smoother transition of a former startup founder from being a job provider to a job seeker. Originality/value : The use of qualitative research methodology for the aforementioned purpose is not very widely discussed and researched especially in the context of Indian startup ecosystem.